The Effectiveness of Web-Based Recitation Program on Improving Students’ Conceptual Understanding in Fluid Mechanics (Jurnal Pendidikan IPA Indonesia, 2020)
A web-based recitation program has been developed to improve students’ conceptual understanding of some fundamental concepts of fluid mechanics. The program consists of multiple-choices conceptual questions followed by immediate feedback for each option. This study aimed to examine the effectiveness of the program and whether the program can be used by students without any assistance of instructor. If it is the case, the program could be used by instructor to serve recitation program outside the classroom. To address the objectives, this study employed a non-randomized control group pretest-posttest design involving three groups of students. The first group (E-1) used the program accompanied by teaching assistant, the second group (E-2) used the program by his/herself without assistance, and the third group (C) learned by his/herself without the program. The study involved 73 students enrolling the introductory physics course in physics education department, State University of Malang, as the subject. The effectiveness of the program was analyzed by comparing N-gain scores of the three groups and the responses of the E-1 and E-2 students to the program. Pretest was administered after the three groups of students have learned fluid mechanics through regular lecture sessions, and the posttest was administered after the E-1 and E-2 groups have finished learning with the help of the program. The results showed that the N-gain of group E-1, E-2, and C was 0.51 (upper medium), 0.58 (upper medium), and 0.12 (low), respectively. The ANOVA test showed that the three N-gain values were statistically different (p = 0,000). The LSD post hoc test showed that the N-gain of group C was significantly different from that of group E-1 and E-2 (p=0.000), whereas the N-gain between group E-1 and E-2 was not significantly different (p=0.244). It can be concluded that the web-based recitation program was effective to improve the students’ conceptual understanding of fluid mechanics and can be used equally well with or without direct assistance from instructor or teaching assistant. The students that used the program also gave quite positive responses to the program, that the program could help them to reflect on the appropriateness of their understanding, was easy to use, and had attractive features.